Antifouling paints based on marine natural products from Colombian Caribbean - Acevedo, Marisol Santos (2013)
Biofouling control involves the application of paints containing toxic substances to the marine ecosystem. One of the most promising alternative technologies to antifouling paints based on heavy metals is the development of coatings whose active ingredients are compounds naturally occurring in marine organisms. This study investigated the antifouling activity of organic extracts from some epibiont-free Colombian Caribbean Sea sponges (Agelas tabulata, Myrmekioderma gyroderma, Oceanapia peltata, Aplysina lacunosa, Neopetrosia sp.) and a sea-cucumber (Holoturia glaberrima). Extracts were incorporated into hard stable gels and into soluble matrix antifouling paints and exposed in the sea (Colombia and Argentina). After 45 and 90 days, significant differences in fouling cover percentages between painted panels and controls were found (p < 0.05). It was demonstrated that the greatest antifouling activity was contained in extracts of A. tabulata and Holoturia glaberrima in both study sites. This study successfully identified potential new sources of natural antifouling compounds.